Instructional Leadership and 21st-Century Pedagogy: Predicting Students' Critical Thinking and Science Performance in Philippine Public Schools - Analyn G. Saucejo; Nhelbourne K. Mohammad (Journal of Educational Technology Innovation and Applications, 2026)
This study examined the predictive influence of school administrators' leadership and 21st-century science learning practices on Grade 9 students' critical thinking and academic performance in science. A quantitative, descriptive-correlational design with a predictive component was employed in 58 public junior high schools in the Zamboanga del Norte Division, Philippines. Data were collected from 58 school administrators, 89 Grade 9 science teachers, and 340 Grade 9 students using validated questionnaires, a critical thinking test, and official school records. Findings revealed that administrators' leadership was "Very High," 21st-century practices were implemented "Often," and students demonstrated "High" critical thinking and "Very Satisfactory" academic performance. Multiple regression analyses showed that learning environment and school culture (β = 0.31, p < 0.001) and instructional leadership (β = 0.28, p < 0.001) were significant predictors of critical thinking, while authentic assessment (β = 0.31, p < 0.001) and integration of critical thinking strategies (β = 0.27, p < 0.001) were the strongest predictors of academic performance. The study provides empirical evidence that school leadership and instructional practices are interconnected drivers of student success. It recommends that administrators prioritize instructional and cultural leadership, and that teachers consistently integrate inquiry-based and cognitively demanding strategies to foster critical thinking and improve science outcomes.